2018 40th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2018
DOI: 10.1109/embc.2018.8512535
|View full text |Cite
|
Sign up to set email alerts
|

Teenagers’ Usage of a Mobile-Wearable-Cloud Platform to Promote Healthy Lifestyles: the PEGASO Experience

Abstract: In contemporary society, non-communicable diseases linked to unhealthy lifestyles, such as obesity, are on the rise with a major impact on global deaths. Prevention is the new frontier, promising to increase life expectancy and quality, while reducing costs related to healthcare. The PEGASO project developed a mobile ecosystem where the digital Companion aims at empowering teenagers in the adoption of healthy lifestyles. The pilot study conducted in three European countries (Spain, UK and Italy) shows a good a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This has been observed in many studies and in particular, in research with adolescents it has been observed that they tend to lose interest in tracking apps or wearable devices after a few weeks ( 45 ). In the PEGASO study, only 20 out of 357 users kept entering their meals in the e-Diary for at least 90 days ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been observed in many studies and in particular, in research with adolescents it has been observed that they tend to lose interest in tracking apps or wearable devices after a few weeks ( 45 ). In the PEGASO study, only 20 out of 357 users kept entering their meals in the e-Diary for at least 90 days ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The intervention included two wearables and an app for monitoring physical activity, a serious game with educational content, an app for exchanging earned reward points for discounts on healthy food and physical activity programs in the participants' city, and the PEGASO Companion, the main app for accessing all the aforementioned apps and services. The Companion ( 36 , 37 ) integrated a virtual coach that provided the user with educational content and tried to keep the user engagement high through gamification techniques, including quizzes, challenges, badges, and points.…”
Section: Methodsmentioning
confidence: 99%
“…The length of study ranged from several days over a period of one week [ 21 ] to nine months [ 31 ]. 21 studies took place within a single country, whilst two studies were conducted over multiple countries [ 16 , 18 ]. The number of included studies conducted in each country are listed in Fig 1 , with five of the included studies conducted in United States.…”
Section: Resultsmentioning
confidence: 99%
“…The other ten studies used proprietary physical tracking wearables developed for the study. Only one study employed the use of a smart garment which was worn by the user during physical activity [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The app includes adolescents' preferences, a technology combination that includes an entertainment, advisory, self-monitoring, and social support tool. However, actual data could not be retrieved for this study (58). The remaining studies utilized text messaging to promote healthy behaviors in children aged 8-10 years (59); investigated the impact of web and mobile technologies for type 1 diabetes therapy (60); the use of short message services (SMS) to promote lifestyle behaviors and psychological wee-being in children aged 7-12 years (61); and the use of mHealth to explore healthy eating in ethnic minority first or second year students (62).…”
Section: Resultsmentioning
confidence: 99%